The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fendo.2021.571568
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis: Association Between Hypoglycemia and Serious Adverse Events in Older Patients Treated With Glucose-Lowering Agents

Abstract: AimsWe conducted a meta-analysis of serious adverse events (dementia, macro- and micro-vascular events, falls and fractures, and death) associated with hypoglycemia in older patients treated with glucose lowering drugs.Materials and MethodsMeta-analysis of studies reporting on hypoglycemia and adverse events. The search included studies from two previously published systematic reviews, and an updated search of MEDLINE and EMBASE from April 2014 to November 2019. We assessed study validity based on ascertainmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 53 publications
0
25
0
2
Order By: Relevance
“…However, one of the included studies was cross-sectional in design, reporting risk of mild cognitive impairment and not dementia [ 11 ]. Another review [ 9 ] published by the same authors in 2019 also demonstrated a statistically significant increased risk of dementia with prior hypoglycemic events (OR: 1.50 95% CI: 1.29, 1.74). Nonetheless, our study is a significant update from their review as we excluded two studies [ 27 , 28 ] from the past review (due to overlapping data) and included three new studies which significantly raised the statistical power of our analysis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, one of the included studies was cross-sectional in design, reporting risk of mild cognitive impairment and not dementia [ 11 ]. Another review [ 9 ] published by the same authors in 2019 also demonstrated a statistically significant increased risk of dementia with prior hypoglycemic events (OR: 1.50 95% CI: 1.29, 1.74). Nonetheless, our study is a significant update from their review as we excluded two studies [ 27 , 28 ] from the past review (due to overlapping data) and included three new studies which significantly raised the statistical power of our analysis.…”
Section: Discussionmentioning
confidence: 91%
“…While hypoglycemia is easily treatable and a transient complication, it is not without other short and long-term adverse effects. Hypoglycemia has been shown to increase the risk of micro and macrovascular complications of DM along with the increased risk of falls and fractures [ 9 ]. Research also suggests a heightened risk of cardiovascular and all-cause mortality due to hypoglycemia in diabetics [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hypoglycemia is an independent risk factor for dementia [ 104 , 105 ]. Treatment with glucose lowering pharmacotherapy has an inherent risk for iatrogenic hypoglycemia, especially in older T2DM patients with a long diabetes duration treated with insulin or sulfonylurea [ 106 ].…”
Section: Cognitive Functionmentioning
confidence: 99%
“… 3 However, intensification of glycaemic treatment increases hypoglycaemic exposure, which is believed to be associated with an increased risk of cardiovascular events. 4 6 As such, guidelines suggest individualising HbA1c targets while also focusing on hypoglycaemic avoidance and acknowledging that more research in this area is required. 7 …”
Section: Introductionmentioning
confidence: 99%